Multilevel Analysis on the Contextual Effect of the Integrated Health Post Activity on Development of Children Under Five in Kubu Raya, West Kalimantan - Lolita, Lolita; Dewi, Yulia Lanti Retno; Murti, Bhisma (Journal of Maternal and Child Health, 2019)
Background: It is estimated that 200 million children in developing countries do not develop optimally. Child development is a complex improvement in body structure and function that include gross and fine motoric, speech, language, socialization, and independence aspects of development. The success of children in achieving optimal development determines the future of a nation. The purpose of this study was to analyze the contextual effect of integrated health post (posyandu) in child development in Kubu Raya District, West Kalimantan. Subjects and Method: This study was a cross sectional conducted at 25 integrated health post in Kubu Raya District, West Kalimantan, from November to December 2018. A sample 200 of children under five was selected by simple random sampling. The dependent variable was child development. The independent variables were maternal age at marriage, maternal education, parental income, parenting style, birth weight, birth length, child development monitoring, child development intervention, and integrated health post strata. Data collection was conducted using questionnaire and analyzed using multilevel logistic regression analysis in Stata 13. Results: Child development disorder increased with early maternal age at marriage (b= 3.18; 95% CI= 0.77 to 5.59; p = 0.010), but decreased with high maternal education (b= -2.22; 95% CI= -3.92 to -0.52; p= 0.010), high parental income (b= -4.01; 95% CI = -6.55 to -1.47; p= 0.002), proper parenting style (b= -2.89; 95% CI= -5.18 to -0.60; p= 0.013), normal birth weight (b= -2.87; 95% CI= -4.80 to -0.95; p= 0.003), normal birth length (b= -3.13; 95% CI= -5.63 to -0.63; p= 0.014), child development monitoring (b= -2.97 95% CI= -5.58 to -0.36; p= 0.025), and child development intervention (b = -3.53; 95% CI= -6.19 to -0.87; p= 0.009). The integrated health post had a contextual effect on child development with ICC= 19.9%. Conclusions: Child development disorder increases with early maternal age at marriage, but decreased with high maternal education, high parental income, proper parenting style, normal birth weight, normal birth length, child development monitoring, and child development intervention. The integrated health post has a contextual effect on child development. Keywords: child development, children under five, multilevel analysis Correspondence: Lolita. Public Health Masters Program, Universitas Sebelas Maret, Jl. Ir Sutami 36A, Surakarta, Central Java, Indonesia. Email : Patricialolita25@gmail.com Seluler: 082328463344. Journal of Maternal and Child Health, 2019, 4(4): 222-229 https://doi.org/10.26911/thejmch.2019.04.04.01